Poverty and Social Exclusion in India - World Bank (Washington, DC, 2012)
The report is organized around three chapters, in addition to this overview, each one dealing with an excluded group: Scheduled Tribe (ST), Scheduled Caste (SC), and women. The objective is to provide a diagnostic of how the three excluded groups under analysis have fared along various development indicators during a period of rapid economic growth in the national economy. In seeking this objective, the report also addresses correlates and the processes that explain how and why these groups have fared the way they have over a period of time. Chapter two in this report focuses on the Adivasis or STs. In most analyses, this topic is addressed after the Dalits, but the author has placed it first for analytical and organizational purposes. There are two reasons for this: tribal groups are not strictly within the caste system, and the bonds of rituals do not affect their relations with the world in general. Also the report shows that outcomes among Adivasis are among the worst, despite considerable variation across places of residence and tribal groupings. Finally, Chapter three focuses on Dalits, a term that has united the SCs in a process that is more empowering than the process of identification by individual names, which have been and continue to be associated with ritually impure occupations.